(3GdTeSjIs - (3Ydj Hf YeQ Hf Ydj GdcGJHj GdbRhjfj, fLe GdOjf, hjbGd dg OHjQGf,J (B675 (3g` s ((3eMeO Hf KGHJ Hf SYjO GdhQjfdGfi s)
(3ChdgG (B:s
(3GdMeO ddg GPi CHOY fXGe GdehLhO hHYO deG cGf HEJaGb Cgd GdYbhd Cf GdYdhe CYdi GdeWGdH aCTGQ ef SYO HWdH GdMb HJMQjQ LGeY dbhGYOg (B( (3jYfi GdefWb (B) (3aHGOQJ debJVi ETGQJg s
(3BNQgG (B:s
(3Yf ehVhYGJgG dEeJfGY Cf jchf MO GdTF eWdhHkG bHhJg GdHQgGf gPG BNQ gPG GdcJH ai gPg GdQSGdI hGddg GdeSJYGf dGQH ZjQg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg cedJ HMeO Gdgd JYGdi hMSf Yhfg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B159s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1063s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs